Going Green: How Consumption Values Lead to Green Consumption Behavior in Z Generation - Fadilla Lastriany; Rezki Ashriyana Sulistiobudi; Marina Sulastiana (Annals of Management and Organization Research, 2021)
Purpose: Consumption of plastic, especially single-use ones, is seen today as one of the leading environmental problems since it is used for a very short time and takes hundreds of years to decompose. At the same time, there has been a growing awareness to consume environmentally friendly products and minimize the use of plastic. Similar research has been conducted but in a limited amount in the Z generation context. This study aimed to identify the correlation between green consumption values and green consumption behavior in the Z generation. Research methodology: The variables in this study were measured using the GREEN scale and the ECCB scale. The collected data was analyzed by using correlational methods. The two-stage cluster-random sampling technique was used, and 202 respondents participated in this study. Results: The results showed that there is a significant positive correlation between green consumption value and green consumption behavior at a moderate level. Five indicators of green consumption behavior correlate to green consumption value (recycled products, biodegradability, driving habits/oil dependency, consumer purchase, and reduction in electricity). Limitations: Limitations related to this study were also discussed as its opportunity for further research. Contribution: These findings will empower people to understand how our value will create green consumption behavior, and it will derive following sustainable buying behavior.